LES MOTS TÉMOINS DE LA NOUVELLE RÉALITÉ. QUELQUES RÉFLEXIONS SUR LE LEXIQUE PANDÉMIQUE. - Woch, Agnieszka (Estudios Románicos, 2022)
The article will focus on the lexical creativity brought about by the coronavirus pandemic. Taking as a reference period the months between February 2020 and December 2021, we will reflect on the functions and the types of lexemes used by the media that subsequently penetrated the everyday vocabulary. We will analyse the mechanisms that led to the creation of new terms based on the "lexicogenic matrices" of Jean-François Sablayrolles and we will evaluate their productivity. The corpus consists of over one hundred entries detected on both "Néoveille", a web platform which tracks neologisms, and on the Internet, and includes mostly playful, sometimes dysphemic terms, along scientific and technical terms. All these lexemes are words that bear witness to the COVID-19 pandemic and express the need to adapt to this unprecedented reality and to categorise it by naming the new phenomena.